Vitex agnus-castus (Chaste tree berry) in the treatment of menopause-related complaints - М. Д. ван Ди; Г. Г. Бургер; Х. Дж. Теэде; К. М. Боун (Publishing House TRILIST, 2019)
Introduction. It is not known exactly from what times Vitex agnus-castus began to be used in medical practice to alleviate the symptoms of menopause, but this practice seems to have a relatively recent history. This article discusses the basis for the use of the Vitex agnus-castus, which is confirmed by the results of pharmacological and clinical studies. Methods. Mechanisms of the potential relevance of the drug in the context of treating menopausal symptoms are studied taking into account the current understanding of the endocrinology and neuroendocrinology of menopause and related symptoms. Conclusions. Considering that the results of carefully conducted randomized controlled trials are insufficient to confirm the use of each individual plant component, the new results of pharmacological studies confirm the role of the Vitex agnus-castus in alleviating the symptoms of menopause, as well as the need for further research